Dietary Strategies by Foods with Antioxidant Effect on Nutritional Management of Dyslipidemias: A Systematic Review - Isabel Medina-Vera; Lizzette Gómez-; Ana Ligia Gutiérrez-Solis; Roberto Lugo; Martha Guevara-Cruz; José Pedraza-Chaverri; Azalia Avila-Nava (MDPI AG, 2021)
Nutrition plays a fundamental role in the prevention and treatment of dyslipidemias and its oxidative-related complications. Currently, there is evidence about the beneficial effects of isolated antioxidants or foods enriched or added with antioxidant compounds. However, the application of the natural foods is more integrated than the analysis of a single nutrient. Our aim is compiling scientific literature regarding the nutritional strategies by foods with antioxidant effect in blood lipids, enzymatic and non-enzymatic antioxidants, and oxidative and inflammatory markers of subjects with dyslipidemia. We searched in MEDLINE/PubMed, Scopus, and Web of Science. From a total of 263 studies screened, 16 were included. Dietary strategies included walnuts, olive oil, raw almonds, G. paraguayase, white sesame, mate tea, Brazil nut flour, red wine, granulated Brazil nuts, grapes, wolfberry fruit, fermented beverage, coffee, orange, and blackberry juices showed significant differences in blood lipids, antioxidant activity, antioxidant enzymes, and oxidative and inflammatory markers. This systematic review compiling scientific studies about dietary strategies using foods with antioxidant effect to improve the antioxidant status in dyslipidemias.